Observations on Citrus Autumn Leaf Drop in the Libyan Jamahiriya - FUDL-ALLAH, ABD EL-SHAFY A. (The Libyan Journal of Agriculture, 2023)
Citrus autumn leaf drop causes severe damage to the sweet orange trees whether they are old or new lines. This condition usually appears during the period from October to January. The first symptom appears as mesophyll collapse particularly on those leaves that developed during the summer (spring flush) and at the tops of the trees. Affected leaves will roll upward, wilt, and drop leaving the petiole for sometime attached to the twig. The petioles soon drop and severe die back of the twigs may take place. This die back seriously affects the blooming of the following season. Natural incidence of this disorder was observed. Some trees of new lines of sweet orange varieties started to show symptoms of this condition within four years from propagation regardless of the rootstock.